The prospects for the World Trade Organisation Agreement on Government Procurement - Davies, Arwel (2000)
This thesis questions the prospects for the World Trade Organisation, Agreement on Government Procurement. This is the most important international agreement seeking to promote cross-border trade in hitherto closed national procurement markets. For the above threshold goods, services and construction services contracts which it covers, the Agreement's principal objective is to require the non-discriminatory treatment of foreign suppliers. It is because of this general insistence on non-discriminatory treatment that the Agreement's membership is limited to 27 of the 134 World Trade Organisation Members. The first theme of this thesis is therefore devoted to explaining this problem of limited membership, and to proposing possible solutions. While the Agreement's limited membership means that it is not yet capable of liberalising international procurement markets among the general WTO membership, the thesis also considers the Agreement's prospects among the major trading partners which have acceded to date. Our second theme therefore explores two of the problematic areas presenting very different difficulties and challenges, which will impact on the Agreement's success among its present and prospective Members. These distinct areas are, firstly, the use of information technology in public contract awards, and, secondly, the need for an effective system of remedies and enforcement.